A method to solve stability problem of nonlinear cylindrical shell under transversal load - Hong, Le Ngoc; Thach, Le Ngoc (Vietnam Journal of Mechanics, 1996)
The stability problem of the cylindrical shell was studied by many researches, but most of those shells were circular. The present article considers a method to determine the critical load of noncircular cylindrical shell with the open or close section. The author used the small parameter method to obtain the stability equation of the shell. Analyzing quality of the solution, author determines the critical value of the transversal load for a shell with an elliptic close cross section and for an open shell.